USING HEAT FROM SOLAR RADIATION TO ENHANCE THE EFFICIENCY OF HOUSEHOLD COMPOSTER FOR HOUSEHOLD FOOD WASTE COMPOSTING - Moolkambil, Wipavee; Semvimol, Noppawan; Pattamapitoon, Thanit; Phewnil, Onanong (Srinakharinwirot University Journal of Sciences and Technology, 2022)
This research aimed to study the effect of heat from solar radiation to enhance the efficiency of the household composter by degrading household food waste into compost. The composter was using 120-liter vertically polypropylene plastic bucket. On the top, a hole was drilled to feed the composting material and designed with a horizontal air inlet below the air inlet above the tank. The airflow rate was 0.35 kg/day. The inside of the composter was set up with 6 aluminum stick stirrers, basket, and an aluminum tray was placed inside for supporting organic materials. The bottom of the composter was tilted to drain the leachate. The household composter could support 27.65 kg of organic waste. Composter Efficiency was studied by adding 1,680 g of composting materials (5 parts of food waste mixed with 2 parts of soil) continuously adding materials for 14 days by placing them in two areas; outdoor and indoor. The results showed that the household composter turned organic waste in the composter to compost after stop adding waste within 14 days, so the degradation period was 28 days. The quality of the compost product, C: N ratio was 5.64 and 8.21%. The moisture content was 33.70% and 44.99%, pH 8.31 and 8.43, electrical conductivity was 1.37 and 1.60 dS/m. Phosphorus was 0.02% equal and potassium was 0.17% and 0.15%, respectively. The outdoor had better efficiency than the indoor. The overall properties of the product can be used to feed the trees. It was shown that the household composter could be used to transform food waste into compost.